Efek Ekstrak Daun Pluchea indica terhadap Hambatan Pertumbuhan Porphyromonas gingivalis - Taufiq Ariwibowo; Meiny Faudah Amin; Putri Nur Pratiwi (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Porphyromonas gingivalis is one of the bacteria causes primary root canal infections. Bacterial elimination using root canal irrigation agents is important in successful root canal treatment. NaOCl as the gold standard is known to have disadvantages such as irritating periapical tissue. Active compounds in Pluchea indicaleaves such as flavonoids, tannins and terpenoids posses antibacterial effects. Objectives: To determine the effect of Pluchea indica leaves extract on P. gingivalis growth inhibition. Method: This study is an in vitro experimental laboratory of  agar well difusion method used Pluchea indica leaves extract in several concentrations (6,25%, 12,5%, 25%, 50%, and 100%) and NaOCl 5,25% as a positive control. The sample in this study was P. gingivalis. Result: This study showed that the diameter of inhibitor zone against P. gingivalis was exists on concentration of 50% and 100%, their values are 10,216 mm and 13,023 mm. The positive control showed an average inhibition zone of 12.803mm. Conclusion: Pluchea indica leaves extract showed antibacterial effect against P.gingivalis at the concentration of 50% and 100%. The 100% concentration had the largest inhibition zone and was equivalent to positive control in inhibiting P.gingivalis.